Assessing the Role of Technology-Driven IP Management Tools in Safeguarding Financial Services Innovation (International Journal of Scientific Research in Science and Technology, 2024)
This article examines the effectiveness of technology-driven intellectual property (IP) management tools in safeguarding financial services innovation. Through a mixed-methods approach combining resource-based view and dynamic capabilities theoretical frameworks with empirical case studies, we analyze how blockchain timestamping, AI-powered patent monitoring, and cloud-based rights management systems enhance legal enforceability and infringement detection. Our findings reveal that these technologies reduce dispute resolution times by 30%, improve competitive intelligence with 85% true-positive rates, and accelerate licensing workflows from weeks to days. However, significant adoption barriers persist, including legacy system integration challenges, data sovereignty concerns under GDPR/PSD2, and specialized skill shortages. We propose a practical implementation roadmap addressing phased adoption, governance frameworks, and vendor management strategies to help financial institutions leverage these tools for sustainable competitive advantage. This research contributes to understanding how technology can enhance IP stewardship in an increasingly digital financial services landscape while navigating complex regulatory requirements.